(untitled) (Research, Society and Development, 2025)
The objective of this study was to analyze the role of nursing in promoting the quality of life of cancer patients, focusing on strategies that favor adherence to treatment, considering emotional, financial, and physical barriers. The research, of an exploratory nature and with a qualitative and quantitative approach, was conducted through an integrative literature review between 2020 and 2025. The results show that humanized care, effective communication, and family involvement are fundamental to reducing emotional, physical, and financial barriers faced by patients. Nursing, by being in direct and continuous contact with the patient, plays an essential role in providing support, active listening, and implementing strategies that promote biopsychosocial well-being. This study contributes to broadening the understanding of the role of oncology nursing in promoting the quality of life of cancer patients, especially with regard to adherence to treatment. The analysis shows how the actions of the nursing team, through the management of physical symptoms and emotional support, positively influence coping with the disease, providing greater comfort and support to the patient throughout the therapeutic process.